Fluid migrations and volcanic earthquakes from depolarized ambient noise - S. Petrosino (Nature Portfolio, 2021)
Deep fluids inside volcanoes disrupt the oscillations of signals produced by wind and sea. Imaging this disruption through space and time allows tracking hazardous fluid migrations leading to earthquakes before they reach the surface.